Calidad de atención y nivel de satisfacción del usuario del servicio de laboratorio del hospital III EsSalud Iquitos año 2024 - Murayari Florez, Janeth Patricia (2025)
Providing quality healthcare services is a significant challenge for hospitals. It is not just about having good facilities, but also about creating an environment of trust and human warmth. It is the people who work in the hospital, with their dedication and empathy, who make a difference in the lives of patients. Caring for the health and well-being of each person is a fundamental right that must always be promoted and protected. In this research study, conducted in 2024, we sought to find and determine the relationship between the quality of care and the level of satisfaction of users of the laboratory service at Hospital III of EsSalud Iquitos. The research work was of an applied type, with a non experimental design, a quantitative approach, with a descriptive-correlational level of study and a cross-sectional or transversal cut. A sample of 384 users was used, the sampling was non-probabilistic for convenience, choosing the users who attended the laboratory service until reaching the sample number. The reliability of the data collection instrument was measured with Cronbach's Alpha, which, according to the range table, determines that the instrument is excellent with a coefficient of 0.941. The descriptive statistical result of the data showed that the study variables, quality of care and level of satisfaction, were valued by the respondents as good at 87% and 88% respectively, and in the results of the inferential statistics the Rho coefficient of Spearman obtained a low direct correlation of 0.154, with a 2-tailed sig. of 0.003, accepting the general hypothesis Hi, which indicates the existence of a significant relationship between both variables. Analyzing the results obtained in the descriptive and inferential statistical processing of data, it is concluded that the majority of users perceive the quality of care and the level of satisfaction as good and in some dimensions as moderately good, but the direct and low coefficient of Spearman's Rho, although significant, shows that there is practically no relationship between both variables, which determines that patients accept infrastructure and care deficiencies as normal, their objective being to be treated in order to continue with their health treatment.